2012
DOI: 10.1371/journal.pntd.0001676
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance and Discriminatory Value of Elevated Liver Aminotransferase Levels for Dengue Severity

Abstract: BackgroundElevation of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) is prominent in acute dengue illness. The World Health Organization (WHO) 2009 dengue guidelines defined AST or ALT≥1000 units/liter (U/L) as a criterion for severe dengue. We aimed to assess the clinical relevance and discriminatory value of AST or ALT for dengue hemorrhagic fever (DHF) and severe dengue.Methodology/Principal FindingsWe retrospectively studied and classified polymerase chain reaction positive dengue pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 26 publications
7
98
1
Order By: Relevance
“…The percentage of positive cases having headache, eye pain and vomiting were significantly higher during the acute phase of the illness than that in the negative cases. These common clinical features in typical dengue infection were also observed in other published studies (Pérez-Guerra et al, 2005;Chuang et al, 2008;Lee et al, 2012). Our laboratory data showed that the percentage of dengue patients with mean elevated level of Aspartate transaminase and Alanine transaminase were significantly higher than that of laboratory dengue negative patients.…”
Section: Journal Of Virology and Microbiologysupporting
confidence: 89%
“…The percentage of positive cases having headache, eye pain and vomiting were significantly higher during the acute phase of the illness than that in the negative cases. These common clinical features in typical dengue infection were also observed in other published studies (Pérez-Guerra et al, 2005;Chuang et al, 2008;Lee et al, 2012). Our laboratory data showed that the percentage of dengue patients with mean elevated level of Aspartate transaminase and Alanine transaminase were significantly higher than that of laboratory dengue negative patients.…”
Section: Journal Of Virology and Microbiologysupporting
confidence: 89%
“…The reversal of alanine transaminase and aspartate transaminase (AST/ALT) ratio is helpful to diferentiate it from other acute viral hepatitis like HAV, HBV, HCV, etc., where this is rarely seen except in alcoholic hepatitis [6].…”
Section: Biochemical Picture Of Liver (Lfts) In Dengue Fevermentioning
confidence: 99%
“…Involvement of liver with deranged liver function tests (LFTs) is likely with dengue fever and which may include mildly raised in serum total bilirubin, increased alanine transaminase (ALT) and aspartate transaminase (AST), and decreased in serum albumin which can be a used as a prognostic indicator [6].…”
Section: Description Of Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Other tests, such as hepatic enzyme dosage, are required when dengue with liver condition is suspected. Rise of aspartate aminotransferase hepatic (AST) and alanine aminotransferase (ALT) enzymes is common in acute infection cases by dengue and increases during the disease´s convalescence period (from the 7 th to the 10 th day) (LEE et al, 2012). Hemogram with platelet counts is a great help in acknowledging the presence of hemorrhagic dengue since the decrease in lymphocytes and platelet counts are associated with this serious type of the disease (BRASIER et al, 2012).…”
Section: Introductionmentioning
confidence: 99%